CORINOS. I. JWST/MIRI Spectroscopy and Imaging of a Class 0 Protostar IRAS 15398–3359 - Yao-Lun Yang; Joel D. Green; Klaus M. Pontoppidan; Jennifer B. Bergner; L. Ilsedore Cleeves; Neal J. Evans II; Robin T. Garrod; Miwha Jin; Chul Hwan Kim; Jaeyeong Kim; Jeong-Eun Lee; Nami Sakai; et al. (The Astrophysical Journal Letters, 2022)
The origin of complex organic molecules (COMs) in young Class 0 protostars has been one of the major questions in astrochemistry and star formation. While COMs are thought to form on icy dust grains via gas-grain chemistry, observational constraints on their formation pathways have been limited to gas-phase detection. Sensitive mid-infrared spectroscopy with JWST enables unprecedented investigation of COM formation by measuring their ice absorption features. Mid-infrared emission from disks and outflows provide complementary constraints on the protostellar systems. We present an overview of JWST/Mid-Infrared Instrument (MIRI) Medium Resolution Spectroscopy (MRS) and imaging of a young Class 0 protostar, IRAS 15398−3359, and identify several major solid-state absorption features in the 4.9–28 μ m wavelength range. These can be attributed to common ice species, such as H _2 O, CH _3 OH, NH _3 , and CH _4 , and may have contributions from more complex organic species, such as C _2 H _5 OH and CH _3 CHO. In addition to ice features, the MRS spectra show many weaker emission lines at 6–8 μ m, which are due to warm CO gas and water vapor, possibly from a young embedded disk previously unseen. Finally, we detect emission lines from [Fe ii ], [Ne ii ], [S i ], and H _2 , tracing a bipolar jet and outflow cavities. MIRI imaging serendipitously covers the southwestern (blueshifted) outflow lobe of IRAS 15398−3359, showing four shell-like structures similar to the outflows traced by molecular emission at submillimeter wavelengths. This overview analysis highlights the vast potential of JWST/MIRI observations and previews scientific discoveries in the coming years.